Gainers and Losers from Market Integration - Hans Gersbach; Hans Haller (Center for Economic Studies and ifo Institute (CESifo), 2019)
We compare integration of economic, matching and networking markets. There can be losers from integration in all three cases, but their relative numbers depend on the type of market. There can be many losers from integration of pure exchange economies. There are relatively few losers from integration of networking markets. In the matching case, the relative numbers tend to lie between those of the other two cases.
Keywords: C78; D02; D85; 330; competitive exchange; matching theory; networks; market integration